MccJ25 C-terminal is involved in RNA-polymerase inhibition but not in respiration inhibition - Vincent, Paula Andrea (2005)
Microcin J25 appears to have two intracellular targets: (1) RNA polymerase, which was described in Escherichia coli and Salmonella enterica serovars, and (2) cell respiration in Salmonella enterica serovars. C-terminal glycine amidation of the threaded segment localized in the MccJ25 lariat ring region specifically blocked the RNA-polymerase inhibition, but not the cell respiration inhibition and peptide uptake. These results suggest that different regions of the molecule are responsible for each cellular effect, they are localized far away from the β-hairpin region and the C-terminal region is an important determinant for RNAP inhibition.